Sports Injuries Among First-Year Female Students at the College of Physical Education and Sports Sciences – University of Baghdad - اليوسفي , شيماء; الشمري , بيداء; النعيمي , فرح (Journal of Sport Science Technology and Physical Activities, 2025)
The research addressed the role of sports medicine and its various branches in serving athletes, particularly first-year female students. It focused on how to prevent potential injuries and provide appropriate therapeutic and rehabilitative services after injuries occur. The importance of early detection whether through pain or observation by researchers and specialized faculty was emphasized to prevent the injury from worsening or becoming critical. The study aimed to identify: The practical lessons during which injuries are most frequent and the timing of their occurrence, The impact of environmental factors, The causes of injuries among first-year female college students, The body parts most susceptible to injury. The descriptive method was used, as it suits the nature of the research, with a sample of 54 students out of a total of 133 first-year female students in the college. After statistical analysis, the researchers concluded the importance of organizing the daily practical lesson schedule, applying preventive measures during practical lessons, gradually increasing the intensity of skills and exercises, and emphasizing the importance of warming up all joints—especially during the winter season